Becoming Europe's Parliament: Europeanization through MEPs' Supranational Activism, 1952–79 - Mechthild Roos (JCMS: Journal of Common Market Studies, 2020)
The European Parliament (EP) – today one of the most powerful actors at EU level – was intended to be a mere consultative assembly at the founding of the European Communities. This article studies the beginnings of the EP's parliamentarization, from its establishment in 1952 to its first direct elections in 1979. The article uses the concept of Europeanization to analyse what ideational, normative and rationalist factors induced MEPs – delegates from the member states' national parliaments at the time – to invest considerable time and effort into an institution that promised no significant political impact, career improvement, or acknowledgement by voters. In so doing, the article demonstrates that despite the fact that careers were made at the national level, MEPs swiftly began to behave as Euro-parliamentarians rather than national delegates. Inside the EP, MEPs were therefore both themselves Europeanized and pushed for the Europeanization of the EP more generally.
Keywords: 330; European Parliament; Europeanization; European integration; parliamentarization; European Community